STEM Clubs: The Promising Space to Foster Students’ Creativity - Anh, Nguyen Thi Van; Bien, Nguyen Van; Son, Dang Van; To Khuyen, Nguyen Thi (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The rapid developments of Science and Technology call for individuals to have strong academic knowledge and creativity. Research shows that students acquire creativity after either curricular or extracurricular activities in subject matters. However, there is not much research examining students’ creativity through integrative learning activities, such as STEM activities. In this current study, we examine the potential of STEM clubs in terms of fostering students’ creativity. We used the survey method to assess students’ creativity in engineering design. We collected the data from 244 Vietnamese students, including members and non-members in STEM clubs. The quantitative analysis was performed to examine the differences between members’ creativity and non-members’ creativity. The results show that STEM club members have significantly more creativity than non-members. The results also show that STEM club members have significantly more creativity than non-members. Based on the results, STEM clubs demonstrate a significant impact on students' creativity. Consequently, STEM clubs should be implemented in high school to enhance students’ creativity.